The moderating effect of risk-taking propensity on the relationship between perception towards insurable risks and general Takaful demand among SMEs - Salleh, Fauzilah; Awang, Zainuddin; Rashid, Norfadzilah; Burhan, Nik Ahmad Sufian (Society of Business and Management, 2021)
This study aimed to evaluate the influence of perception towards insurable risks on the general Takaful demand via risk-taking propensity among small and medium enterprises (SMEs) in Malaysia. This study presented essential insights that would benefit Takaful operators in determining and enhancing general Takaful demand among SMEs. Studies have identified two major factors of risk behaviour that influence general insurance demand, which are the perception towards insurable risks (independent variable) and risk-taking propensity (moderator). This study presented theoretically significant information on the incorporation of perception towards insurable risks and risk-taking propensity to explain the general Takaful model. For this study, a total of 278 SMEs in Malaysia were sampled. All gathered data were analysed using AMOS for the testing of hypotheses. The results of structural equation modelling (SEM) revealed perception towards insurable risks as the key factor that drives the general Takaful confidence in decision making and risk-taking propensity as a moderator in the relationship between the perception towards insurable risks and general Takaful demand. Apart from providing a clearer overview of Takaful demand among SMEs in Malaysia, the obtained findings of this study also highlighted the significance of healthy and ethical behaviour in decision making in order to protect the organisational resources and accomplishments.